Genetic and phenotypic parameters evaluation for body weight, conformation and production traits of indigenous Uttara using MMLSML - SINGH, M K; KUMAR, S; SHARMA, R K; SINGH, S K; SINGH, B; SINGH, D V (The Indian Journal of Animal Sciences, 2019)
The present study was undertaken to investigate correlations between body weight, conformation and production performance of indigenous Uttara chickens. The data collected for different periods from the birds were produced using 25 sires and 200 dams through pedigreed mating. The birds were maintained on a sire family basis, consisting of 25 sire families with a male to female ratio of 1:8. Genetic and phenotypic correlation were estimated between different traits at different period and showed varying levels of correlation estimates. The results indicated that indigenous Uttara chickens have all the attributes of commercial bird for rural poultry production and to be used as a dual purpose bird for low input free range system of rearing as evidenced by its size and egg production.